Barriers to nurse-patient communication in primary healthcare centers in Bahrain: Patient perspective - Nada Mahmood Abdulla; Rula Jamal Naqi; Ghufran Ahmed Jassim (Elsevier, 2022)
Objectives: Effective and efficient communication is a core element in healthcare systems, especially between healthcare providers and patients. This study aimed to identify communication barriers between nurses and patients in primary healthcare centers in Bahrain. Methods: This is a cross-sectional study conducted across primary healthcare centers in Bahrain. Four hundred and two patients were recruited using convenience sampling. A self-administered questionnaire comprising 29 items on communication barriers was used. Results: A total of 402 patients consented to participate. The majority of participants reported the following statements had large effects on communication: "shortage in the number of nurses compared to the large number of patients" (254/401, 63.3%), "lack of desire of nurse to communicate with patients" (246/402, 61.2%), and "negative attitude of the nurse toward the patient" (238/401, 59.4%). Further, "difference in language between nurses and patients," "lack of self-confidence by nurses," and "nurses overwhelmed by work" were ranked as top three statements with a significant influence on communication between nurses and patients. Conclusions: Communication between healthcare providers and patients is pivotal for an optimal healthcare service. Based on the findings of this study and the literature, we recommend formal training of health care workers in improving communication skills and including this not only in medical curriculum but also in the form of continuing medical education (CMEs)1.1 The abstract for this research article was submitted to the annual research conference 2021 at the Royal College of Surgeons in Ireland, Medical University of Bahrain and was not submitted for publication elsewhere prior to publication.